A CASE OF SIMULTANEOUS HEPATIC, SMALL INTESTINAL, AND ADRENAL CAVERNOUS HEMANGIOMAS - VISRUTARATNA, Pannee; AUEPITAKSAKUL, Wattanawan (The ASEAN Journal of Radiology, 2023)
We report a case of multiple cavernous hemangiomas of the liver, small intestine, and left adrenal gland. A 29-year-old woman was found to have multiple hemangiomas of the small intestine during an exploratory laparotomy for acute abdominal pain. After surgery, abdominal CT scans showed multiple hemangiomas in the liver, small intestine, and left adrenal gland. A barium study showed multiple polypoid filling defects in the duodenum, jejunum and ileum, which were hemangiomas.